Embodied carbon in traded goods trade and climate Change seminar, June 18-20, 2008, Copenhagen, Denmark) - Kejun, Jiang (International Institute for Sustainable Development, 2008)
The term "embodied carbon" refers to carbon dioxide emitted at all stages of a good's manufacturing process, from the mining of raw materials through the distribution process, to the final product provided to the consumer. Depending on the calculation, the term can also be used to include other GHGs as well. Important questions in climate change and international trade discussions are linked to embodied carbon. Should emissions be allocated at the point of consumption (meaning a calculation like embodied carbon), or at the point of manufacture (meaning a calculation like those currently performed for the purposes of the Kyoto Protocol)? Should international trade be considered in a future climate change agreement to avoid "carbon leakage" to developing countries?